Influence of mechanical anisotropy on shear fracture development - Gómez-Rivas, E.; Griera, A. (TRABAJOS DE GEOLOGÍA, 2009)
Analogue models have been used to investigate the influence of the orientation of a planar mechanical anisotropy on the development of shear fractures. Anisotropic plasticine models with the anisotropy planes initially oriented at different angles with respect to the deformation axes have been deformed under pure shear boundary conditions. Two sets of shear fractures are formed in all the experiments. Their asymmetry depends on the initial orientation of anisotropy. In oblique cases the local stress field inferred from fracture sets differs from the stress field applied by the deformation apparatus. The degree of anisotropy can be estimated from the differences between both stress fields using a simple analytical method.